(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The aim of this research is to apply the concept of total value management to improve the process design of producing the toothpaste in Al Mammon factory one of the in the general company of food industry. The concept of total value management is concerning with achieve more than one values which are important for the customers as these values are related to the customers satisfaction. The research problem is that the factory did not measure the effectiveness of process design as this company has weakness in analyzing this effectiveness in synchronies with total value management. On the other side, the company did not give more attention to the cost of products and selling prices within the value cost/ profit which is one of the total value management values. This research is based on one basic hypothesis which is that applying total value management can improve the process design of producing the toothpaste. The research reached to some conclusions: the effectiveness of process design is low and it is not relevant to the goal of process objective of productivity, efficiency, cost, time and utilization. Also, the research concludes that applying the concept of total value management through using cost/profit values will improve the effectiveness of process design of toothpaste. The research recommends that the company should apply total value management through using cost/profit values will improve the effectiveness of process design of toothpaste.